The Conceptual Framework of Innovation Development in the Enterprise Management System - Bondarenko Svitlana A. (Problemi Ekonomiki, 2016)
The aim of the article is to define the main conceptual framework of innovation development in the enterprise management system on the basis of the systemic approach. The current state of the innovation activity of industrial enterprises and results of introducing innovations in Ukraine have been analyzed, which revealed the absence of an effective system of innovation activity at enterprises. This results from insufficient financial resources, lack of motivation for the enterprise to introduce innovations, unpreparedness of resource provision of innovation process, unformed specific competences for the innovation activity. Besides, the vague state policy on innovation development, lack of efficient mechanisms for its stimulation and provision hinder the practical implementation of the innovation development system at enterprises. The author’s study of modern concepts of innovation development allowed to specify the author’s concept of innovation development in the system of enterprise management. It is proved that management of the enterprise innovation activity is a separate type of management activity and requires an appropriate support. The innovation system including functional, process and executive units is presented as a dynamic model of the enterprise innovation activity. The proposed conceptual approaches give a generalized idea about the place of innovation development in the system of enterprise management